Rapid screening of lipase inhibitors in licorice extract by using porcine pancreatic lipase immobilized on Fe3O4 magnetic nanoparticles. Issue 12 (21st May 2021) - Zeng, Fei; Wu, Wenxing; Zhang, Yiying; Pan, Xin; Duan, Jinao
Abstract : Lipase inhibitors from G. inflata extracts were screened by using porcine pancreatic lipase immobilized on magnetic nanoparticles. In addition, the structure–activity relationship of the eight identified chalcones was studied. Abstract : Chalcones, a class of natural lipase inhibitors, have received substantial attention from researchers in recent years. Although many kinds of chalcones are typically distributed in G. inflata, there is little literature about the anti-lipase activity of G. inflata extracts (GIEs). In the present study, a ligand fishing strategy for fast screening of lipase inhibitors from GIEs was thus proposed. Porcine pancreatic lipase (PPL) was firstly immobilized on carboxyl modified Fe3 O4 magnetic nanoparticles (MNPs) to obtain PPL functionalized MNPs (PPL@MNPs), and then the PPL@MNPs were incubated with a bioactive fraction to fish out the ligands. Eight ligands were obtained and identified as one flavone together with seven chalcones. Licochalcone A, licochalcone D and licochalcone E inhibited pancreatic lipase (PL) with IC50 of 4.9, 3.2 and 5.8 μM, respectively. Meanwhile, investigation of the structure–activity relationship also revealed that isopentenyl and hydroxyl substituents at ring A were essential for the noncovalent inhibitory potency of the chalcones.